A Prospective Study on the Systematic Application of the Safe Insertion Umbilical Venous Catheter (SIUVeC) Bundle - Giovanni Barone; Gina Ancora; Mauro Pittiruti; Giorgia Prontera; Giovanni Vento; Vito D’Andrea (Children, 2025)
Background/Objectives: Inserting umbilical venous catheters is a common procedure in neonatal intensive care units. However, this maneuver is potentially associated with early and late complications, some of which can be severe. Several strategies have been described in the literature to minimize the risk of such complications. The recently described SIUVeC (Safe Insertion Umbilical Venous Catheter) protocol incorporates all the innovations suggested by the latest literature, with the intention of reducing the risk associated with this procedure. The purpose of this paper is to report the outcomes of the systematic implementation of this protocol. Methods: Infants were enrolled in this prospective study if they were eligible for umbilical venous catheter placement. Results: A total of 449 infants were enrolled in the study. In total, 407 (90.6%) catheters were successfully placed in the proper position, at the inferior cavo–atrial junction. A total of 89.9% of the catheters were removed electively, without any complications. Conclusions: The SIUVeC protocol demonstrates an effective strategy for the safe elective insertion of umbilical venous catheters.